$\displaystyle 3 = 3 e^{\ln \left(1/\sqrt{3}\right)} + e^{\ln \sqrt{3}} = \frac{3}{\sqrt{3}} + \sqrt{3} = 2 \sqrt{3}$ How do u get this?
Follow Math Help Forum on Facebook and Google+
Originally Posted by maybeline9216 $\displaystyle 3 = 3 e^{\ln \left(1/\sqrt{3}\right)} + e^{\ln \sqrt{3}} = \frac{3}{\sqrt{3}} + \sqrt{3} = 2 \sqrt{3}$ How do u get this? The LHS must be y, not 3. e^[ln(y)] = y e^[ln(1/3)] = 1/3 So, e^[ln(1/sqrt(3))] = 1/sqrt(3) Thus, y = 3/sqrt(3) +sqrt(3) y = sqrt(3) +sqrt(3) y = 2sqrt(3)